"I Have More Courage Now": Students' Perceptions of Content Learning and the Development of Their English Self-Concept During the Pre-DP Year - Roiha, Anssi; Salonen, Elise; Salminen, Jenna; Kivimaki, Riia; Laakkonen, Eero (MDPI, 2025)
This study investigates students’ (n = 30) experiences of the pre-Diploma Programme (pre-DP) year in Finland. We examined how the students perceived the impact of English-medium teaching on their content learning, how their English self-concept had evolved during the year and what factors had contributed to this. The data were collected by initial and follow-up questionnaires and semi-structured interviews. The students’ content learning had become easier during the year. In addition, the students had a relatively strong English self-concept already when entering the pre-DP and it had further strengthened during the year. Oral skills were the area that the students highlighted as having improved the most. Becoming used to using English and peer influence were cited as the main factors contributing to this. The study provides important preliminary insights into students’ experiences of learning through a foreign language in the pre-DP year in relation to content learning and English self-concept.